2023
DOI: 10.21037/jtd-23-10
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the risk factors for postoperative delirium in patients with acute type A aortic dissection

Abstract: Background: Delirium is a common postoperative complication of acute type an aortic dissection, which is a serious threat to the patient's life after operation. However, there are many risk factors for delirium and there are different conclusions. The aim of this study was to systematically analyze the risk factors for postoperative delirium in patients with acute type a aortic dissection by means of meta-analysis. Methods: Literature related to the risk factors of postoperative delirium in patients with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Crawford et al [24] reported that a study of head and neck oral cancer in the West of Scotland found that male patients were more likely to develop POD than female patients. A systematic evaluation of risk factors for POD in Stanford type A aortic coarctation suggested that the risk of POD in male patients was 1.33 times higher than in women [25]. However, the gender factor is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Crawford et al [24] reported that a study of head and neck oral cancer in the West of Scotland found that male patients were more likely to develop POD than female patients. A systematic evaluation of risk factors for POD in Stanford type A aortic coarctation suggested that the risk of POD in male patients was 1.33 times higher than in women [25]. However, the gender factor is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few data regarding SCI in ATTAD. One study reports that 1% of patients presenting with ATAAD have SCI [25] A systematic meta-synthesis literature review found 67 cases of SCI caused by aortic dissection (type A and type B). Out of 19 patients having undergone emergency surgery, full recovery in 13 patients, residual paraplegia in 4 patients, and death in 2 patients was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative delirium is a severe brain disorder characterized by inattention, disturbed thinking and altered levels of consciousness [25,26]. A meta-analysis of 12 studies from 2016 to 2022 found that low oxygen levels, prolonged mechanical ventilation, renal dysfunction, low hemoglobin levels and prolonged intensive care stay are risk factors for PD in ATAAD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair of dissection located in the ascending aorta and aortic arch affect cerebral perfusion, so the incidence of POD is higher than in other cardiac operations [8]. Chinese literature publications [9][10][11] report an incidence rate of 21.95%~55.68%, and other countries' publications [12,13] report an incidence rate of 8.00%~52.00%. Once a patient develops POD, the risk of nosocomial infection is increased, an increase is also seen in mortality rate and medical expenses [14], as well as extended hospital stay by 2 to 3 days [15].…”
Section: Introductionmentioning
confidence: 99%